Myopic reliance on natural resources: How African countries can diversify inward FDI - Abdoul' Ganiou Mijiyawa (Columbia University, Vale Columbia Center on Sustainable International Investment (VCC), 2013)
Most of Africa's inward foreign direct investment (IFDI) flows occur in the natural resources sector (i.e. mining, oil and gas). However, Africa has the potential to attract IFDI into other sectors such as labor-intensive manufacturing, agro-processing and services. To improve their attractiveness as destinations for more diverse IFDI, African countries must address two deficits: the infrastructure deficit and the skills deficit.
Keywords: 330